Changing cult values and their impact on conservation history in Czechoslovakia - Zuzana Bauerova (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The paper examines how conservation concepts responded to several significant political, ideological and social changes in Czechoslovakia between 1918 and 1992. With its description of changing cult values, it demonstrates cultural dynamics and paradoxes presented in official state preservation with direct impact on conservation theory, and contributes to broad discussions aimed at relativistic interpretation of cultural heritage.